THE ROLE OF KNOWLEDGE MANAGEMENT PROCESSES IN ENHANCING ORGANIZATIONAL REPUTATION AN EXPLORATORY STUDY OF THE OPINIONS OF A SAMPLE OF WORKERS IN THE GOVERNANCE OF SALAH AL-DIN GOVERNORATE - Dr. Ahmed Jadaan Hammad (Scholar Express Journals, 2023)
The research aims to measure the role of knowledge management processes (knowledge diagnosis, knowledge generation, knowledge storage, knowledge distribution, knowledge application) in enhancing organizational reputation (emotional attractiveness, leadership and vision, environmental performance, financial performance, social performance). The main research problem is the following question. (What is the role of knowledge management processes in enhancing organizational reputation) The research stems from the hypothesis that there is a correlation and influence relationship between knowledge management processes and organizational reputation, and the descriptive analytical approach was adopted in the research. Reached (148) individuals, relying on the statistical program (SMART PLS 3), and the research reached a set of results, the most important of which is the existence of a correlation and influence relationship between knowledge management processes and organizational reputation, but the recommendations recommended by the research is to pay more attention to knowledge management processes for the purpose of enhancing organizational reputation.
Keywords: Knowledge management processes; organizational reputation